LUFTBAREN KULA: Danske feltomitologers tilegnelse af fugle - Liep, John (Tidsskriftet Antropologi, 2019)
John Liep: Airbourne Kula. The Appropriation of Birds by Danish Fieid Ornithologists Against a background of general attitudes toward birds in the Danish public and the historical development of popular omithology the article discusses the practices and strategies of fieid omithologists. Their community is seen as a fieid of practice in which certain values are diffused and acknowledged. A specific development is “hit-hunting” or “twitching” where omithologists collect observations of rare birds. This may evolve into a consuming passion and involves the use of sophisticated communication equipment and considerable expense. Two theories of consumption are used to understand these practices. In one consumption is regarded as a means of competing for status and esteem. In the other it builds on an inner urge for selffulfillment believed to take place through possession of coveted objects. These strategies are not confined to the modem West but are found also in the famous kula exchange in Melanesia.